HEALTHY AGEING AT HOME: ERGONOMICS ADAPTATIONS OF INTERIOR DESIGN AND SELF-ASSESED QUALITY OF LIFE OF OLDER ADULTS OF THE MUNICIPALITY OF LJUBLJANA - Hrovatin, Jasna; Pišot, Saša; Plevnik, Matej (Annales Kinesiologiae, 2017)
<span style="font-size: 11pt; font-family: 'Calibri',sans-serif; line-height: 107%; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"><span style="font-size: 10pt; font-family: 'Arial',sans-serif; line-height: 107%; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Population is ageing and many nations already respond by developing and promoting special strategies of healthy ageing. Living environment is one of the factors that can contribute to healthy and safe ageing at home, providing that it is well adapted to the needs of older adults. On the contrary, it can cause stress, discomfort and lead to injuries, resulting in the loss of independence and autonomy. With the use of a questionnaire, conducting a survey and an analysis regarding the adaptability of living environment to the needs of older adults, we obtained an insight into the quality of living environment of the elderly. In the Quality of Life Survey as a part of the A-Qu-A questionnaire, the participants were 198 older adults with an average age of 71.5 ± 5.2 years of age. Further on, 83 of them participated in the study of the “Adaptation of the Living Environment to the Needs of Older People,” carried out in the homes of the participants, (with an average of 76 ± 1.2 years of age). The results showed that there is a significant difference between the subjective evaluation of the participants and the evaluation by the professionals regarding the estimation of appropriate lighting. The participants who estimated their quality of life as better are more likely to have sufficient or adequate lighting and more adaptations in the kitchen, which makes daily kitchen work easy and safe. Further investigation dealt with the ergonomic adaptation of the bathrooms, where we found out that less than 15 % of the participants installed the handrails in the shower or bath tub, which can significantly contribute to safety. Additionally, physical capability as part of quality of life negatively correlates with the number of adaptations made in bathroom (r = -0.149; p = 0.039), which refers to the fact that the adaptation of accessories (handrails) were only installed when the need for them appeared. With minor changes in the living environment and taking care for maintaining psycho-physical capabilities, older adults can easily and safely perform everyday tasks, which prolongs an individual’s autonomy and independence − the fact we are still not sufficiently aware of.